RESEARCHING STUDENTS’ ORAL PERFORMANCE: What’s wrong with their use of grammar, vocabulary and pronunciation? - Amiruddin Amiruddin (Universitas Islam Negeri Banda Aceh, 2019)
This study was conducted to investigate errors in oral performance among the third year English Education Department students of UIN Ar-Raniry. It was aimed at two folds of research objectives. First, it sought to investigate the most frequently-committed error of the third year English Education Department students of UINAr-Raniry. Second, it attempted to identify the causes of students’ errors in their oral performance. This study employed qualitative research methods. The participants of this study were 20 students registering in Public Speaking Course. To investigate the students’ errors, a speaking test was used as a research instrument. The test was in the form of individual speaking performance on a topic of “Do we need native speakers in our Tarbiyah Faculty?” The participants were required to speak about the issue, which lasted for 10 minutes each. 20 oral performances were transcribed to enable the analysis of the errors. To analyze the student’s oral performance errors, the content analysis was used. This process was followed by analyzing the different aspects of language: grammar, pronunciation, and categories of error causes in communication. The results revealed that puzzling vowel insertion was the most commonly committed error (316/62.7%) compared to shifts in tense (10/2.0%), word order (19/3.8%), subject verb agreement (14/2.8%), and case of referent (15/3%). These errors were identified to have been caused by interlanguage factor. In an effort to respond to these compelling issues in the students’ speaking performance, lecturers who teach English at the University are required to give their maximum attention in order to improve their students’ oral performance.